Triumfetta rhomboidea (Tiliaceae), nueva cita para la flora de Paraguay y el sur de Brasil - Ferrucci, María Silvia; Lattar, Elsa Clorinda (Instituto de Botánica del Nordeste, 2006)
Triumfetta rhomboidea Jacq. se cita por primera vez para Paraguay Oriental y sur de Brasil. Esta especie se describe e ilustra, y se menciona su distribución geográfica en América. Se la compara con T. semitriloba Jacq., la especie más afín.

Triumfetta rhomboidea Jacq. is recorded for the first time from eastern Paraguay and South of Brazil. The species is described and illustrated and its geographical distribution in America is also given. The relationships with T. semitriloba Jacq., a closely related species is considered.
Triumfetta rhomboidea (Tiliaceae), a new report for the flora of Paraguay and south of Brazil
Keywords: Taxonomía; Paraguay oriental; Sur de Brasil; Taxonomy; Eastern Paraguay; Southern Brazil